Which stand development scenario is more suitable for maritime pine stands management in centre inland of Portugal? - Alegria, C.M.M. (2011)
Poster apresentado na IUFRO Conference - Mixed and Pure Forests in a Changing World, que decorreu de 6 a 8 deOutubro na Universidade de Trás-os-Montes e Alto Douro, em Vila Real.